Sentence Alignment as the Basis For Translation Memory Database - Seljan, Sanja; Gašpar, Angelina; Pavuna, Damir (2007)
Sentence alignment represents the basis for computer-assisted translation (CAT), terminology management, term extraction, word alignment and cross-linguistic information retrieval. Created out of the sentence alignment process, translation memory (TM) represents the basis for further research in translation equivalencies. Automatic sentence alignment, based on parallel texts, faces two types of problems: robustness and discrepancies between source and target text in layout and omissions which have influence on the accuracy of the alignment process. The aim of the paper is to present the research of the sentence alignment process realized on the Croatian-English parallel texts (laws, regulations, acts and decisions) and implemented by the alignment tool WinAlign 7.5.0 by SDL Trados 2006 Professional. The alignment process and its impact on creation of translation memories has been presented through comparison of translation memories that distinguish regarding levels of an expert intervention in the set up of the alignment program and preparation of the source text for the segmentation. Recommendations for further development using statistical analysis, automatic learning techniques and language knowledge are suggested.
Projekt MZOS
ENG